Monitoring and Review of Regional Regulations in Indonesia that Ensure Legal Certainty - Mulyawan, Agus; Faishal, Achmad; Suprapto, Suprapto; Saprudin, Saprudin (Journal of Progressive Law and Legal Studies, 2025)
This research aims to analyze the monitoring and review of regional regulations to ensure the relevance, effectiveness, and harmonization of local legal products with the needs of the community and the prevailing legal hierarchy. The absence of clear provisions regarding the mechanisms for monitoring and reviewing in Law No. 12 of 2011 concerning the Formation of Laws and Regulations hinders the realization of a harmonious and consistent legal system. This study employs a normative legal approach, analyzing theories of legal certainty, utility, legal systems, and legisprudence. The findings indicate that Law No. 12 of 2011 on the Formation of Laws and Regulations, as amended by Law No. 15 of 2019 and Law No. 13 of 2022, only regulates the monitoring and review of statutes (laws), without encompassing subordinate regulations, including Regional Regulations (Perda). The study reveals a legal vacuum regarding the mechanisms for monitoring and reviewing Perda, which leads to ambiguities in authority, procedures, and the implementation of evaluations across different levels of government. Consequently, the process is often conducted subjectively, without a uniform and systematic legal reference. To establish a regulatory model for the monitoring and review of Perda that ensures legal certainty, an integrated approach is required—one that combines normative juridical, evaluative-participatory, and data-based methodologies. In this context, three applicable models are identified: (1) a model that adopts the existing monitoring mechanism for statutes; (2) the Regulatory Impact Analysis (RIA) model; and (3) the ROCCIPI analysis model (Rule, Opportunity, Capacity, Communication, Interest, Process, and Ideology). Furthermore, the selective review approach within the Sunset Clause model may be integrated into both the RIA and ROCCIPI frameworks to strengthen the effectiveness of periodic and systematic evaluations of Perda.